Building a transdisciplinary expert consensus on the cognitive drivers of performance under pressure: An international multi-panel Delphi study - Albertella, Lucy; Kirkham, Rebecca; Adler, Amy B.; Crampton, John; Drummond, Sean P. A.; Fogarty, Gerard J.; Gross, James J.; Zaichkowsky, Leonard; Andersen, Judith P.; Bartone, Paul T.; Boga, Danny; Bond, Jeffrey W.; et al. (Frontiers in Psychology, 2023)
The ability to perform optimally under pressure is critical across many occupations, including the military, first responders, and competitive sport. Despite recognition that such performance depends on a range of cognitive factors, how common these factors are across performance domains remains unclear. The current study sought to integrate existing knowledge in the performance field in the form of a transdisciplinary expert consensus on the cognitive mechanisms that underlie performance under pressure. International experts were recruited from four performance domains (i. Defence; ii. Competitive Sport; iii. Civilian High-stakes; and iv. Performance Neuroscience). Experts rated constructs from the Research Domain Criteria (RDoC) framework (and several expert-suggested constructs) across successive rounds, until all constructs reached consensus for inclusion or were eliminated. Finally, included constructs were ranked for their relative importance. Sixty-eight experts completed the first Delphi round, with 94% of experts retained by the end of the Delphi process. The following ten constructs reached consensus across all four panels (in order of overall ranking): 1) Attention; 2) Cognitive Control—Performance Monitoring; 3) Arousal and Regulatory Systems—Arousal; 4) Cognitive Control—Goal Selection, Updating, Representation & Maintenance; 5) Cognitive Control—Response Selection & Inhibition/Suppression; 6) Working memory—Flexible Updating; 7) Working memory—Active Maintenance; 8) Perception and Understanding of Self—Self-knowledge; 9) Working memory—Interference Control, and 10) Expert-suggested—Shifting. Our results identify a set of transdisciplinary neuroscience-informed constructs, validated through expert consensus. This expert consensus is critical to standardising cognitive assessment and informing mechanism-targeted interventions in the broader field of human performance optimisation.